Kingdom of the Netherlands-Netherlands Antilles : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
This 2005 Article IV Consultation for the Netherlands Antilles' reports that economic growth has been feeble so far in this decade, in the midst of economic policy drift. Growth has been constrained by still inflexible labor markets, widespread state ownership and interference in commercial activities, and insufficient investment in infrastructure and human capital. At the same time, free migration to the Netherlands has kept wages high. Persistent budget deficits and a large and growing public debt have also remained unaddressed.